Epicurus’ Swerve and the Randomness Objection to Free Will - Keršys, Matas (Literatūra, 2022)
Modern opponents of free will often aim to demonstrate its unviability by employing the standard argument against free will, which claims that either determinism or randomness is true, and that both options preclude free will. It is frequently assumed that Epicurus defended free will by positing the swerve as a third, uncaused type of atomic motion. This makes Epicurus vulnerable to criticism via the standard argument by seemingly committing him to randomness. This paper asks whether Epicurus can avoid the criticisms of the standard argument and seeks to show that he is not as vulnerable as first appearances indicate. A closer look at De Rerum Natura 2.251–293 reveals the important role of the independent deliberating mind in acts of free volition, while the claim that free volitions are a basic, sense-perceptible aspect of reality raises the question as to whether the swerve really was Epicurus’ main defence of free will.
Keywords: free will; determinism; Epicurus; Lucretius; atomism; mind; emergence